Pengaruh Tingkat Religiositas Terhadap Psychological Well-Being Narapidana Kasus Narkotika di Lembaga Pemasyarakatan Narkotika Jakarta - Yonastasya, Shelomita; Setio, Hezlyn Zakeshia; Valentia, Eveline; Basaria, Debora (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
Life in prison often causes psychological distress for prisoners, such as difficulty accepting themselves and a sense of helplessness. Religiosity can be a factor that helps face these challenges and improve psychological well-being. This study aims to determine the significant influence between religiosity and psychological well-being in prisoners of narcotics cases. This quantitative study involved 115 male prisoners, with data collection using non-probability sampling method and analyzed through IBM SPSS 27. The instruments used were The Centrality of Religiosity Scale (? = .914) and Psychological Well-Being Scale (? = .779). The regression test results show that religiosity has an effect of 18.1% on the psychological well-being of prisoners in the Jakarta Narcotics Prison. This finding shows that religiosity is one important aspect in supporting psychological well-being, although there are other factors that play a role.